Pemberdayaan Masyarakat Berbasis Teknologi Tepat Guna Melalui Instalasi Pengolahan Air Bersih Skala Rumah Tangga di Dusun Kulim Jaya Kabupaten Rokan Hulu - Ika Daruwati; Sischa Febriani Yamesa Away; Saiful Anwar (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to increase the knowledge and skills of Kulim Jaya Village residents in making simple clean water filters on a household scale so that they can get access to clean water more easily. The method of implementing this service used participatory training. The service evaluation instrument was an observation sheet and was analyzed descriptively. The results of this service showed that this simple household-scale clean water filter was able to overcome clean water problems, and there was an increase in residents' knowledge and skills in making clean water filter equipment to overcome clean water difficulties. This simple, clean water filter tool makes it easier for the people of Kulim Jaya Village residents to obtain and increase clean water for their daily needs.